1986
DOI: 10.1021/ac00121a057
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-linked immunosorbent assay for paraquat and its application to exposure analysis

Abstract: several areas of potential concern. Paraquat spray drift of over 200 m from the source can severely damage nontarget plants ( 20). An EPA advisory opinion regarding paraquat use

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 37 publications
(34 reference statements)
1
33
0
Order By: Relevance
“…The affinity of Ab1812 was also related to the steric structure of analytes; for example, compound 49 with a methyl at each side of 4-nitrophenol gave an 1 6 0 of 1820 nM, which is 28 times greater than that (64 nM) of 3-methyl-4-nitrophenol. This key-lock principle has been observed in many immunoassays (Huber and Hock, 1985;Nagao et al, 1989;Newsome and Collins, 1989;Van Emon et al, 1986).…”
Section: Resultsmentioning
confidence: 72%
“…The affinity of Ab1812 was also related to the steric structure of analytes; for example, compound 49 with a methyl at each side of 4-nitrophenol gave an 1 6 0 of 1820 nM, which is 28 times greater than that (64 nM) of 3-methyl-4-nitrophenol. This key-lock principle has been observed in many immunoassays (Huber and Hock, 1985;Nagao et al, 1989;Newsome and Collins, 1989;Van Emon et al, 1986).…”
Section: Resultsmentioning
confidence: 72%
“…It is essential to understand and control the conditions and reactions that lead to the variable relative abundances of these ions if this technique is to become the basis for an environmental analytical method for these herbicides and related substances. J Am Soc Mass Spectrom 1996,7, 981-986 Existing analytical techniques for these herbicides include chemical reduction to produce derivatives amenable to gas chromatography [7], immunoassay [8), separation by CE with UV absorbance detection [9), and square-wave voltammetry [10). However all of the existing techniques are limited in their capabilities because they require an additional chemical derivatization step or special immunoassay reagents or use nonspecific detectors that are subject to false positive results.…”
Section: Capillary Electrophoresis Migration Time Measurementsmentioning
confidence: 99%
“…LC-MS is a promising technique but requires extensive instrumentation. Alternatively, an enzyme-linked immunosorbent assay (ELISA) can satisfy the demands for faster, cheaper and more sensitive analytical methods for use in large scale field studies (Van Emon et al 1986), Koivunen et al (2005) reported an ELISA method for determining paraquat ion with an LOQ of 2 ng/mL in urine samples. The LOQ in urine with the ELISA method in this study is 5- to 25-fold more sensitive than the LOD levels in urine reported in previous paraquat biological monitoring studies (Chester and Woollen 1981; Staiff et al 1975; Swan 1969; Van Wendel de Joode et al 1996; Wojeck et al 1983).…”
Section: Introductionmentioning
confidence: 99%